In Vitro Stimulation of Hamster Lymphocytes with Concanavalin A - Singh, S. B. (1972)
The in vitro response of hamster lymphocytes to concanavalin A (Con A) was investigated by using the (3)H-thymidine incorporation assay, and the results obtained were compared to those with phytohemagglutinin (PHA-P). The optimum culture conditions for stimulation were obtained when one million lymph node cells were cultivated for 72 hr in 2 ml of RPMI-1640 medium supplemented with 10% heat-inactivated fetal calf serum in the presence of either 2 μg of Con A or 0.05 ml of PHA-P. The average ratios of stimulation using lymph node cells with Con A and PHA-P were 227 and 14, respectively. Bone marrow and thymus cells responded very poorly or not at all. Methyl α-d-glucopyranoside, when added to the culture medium at the time of addition of Con A, completely inhibited stimulation. The lymphocyte stimulation could be reversed by addition of the sugar as late as 18 hr after the addition of Con A. The lymphocyte response from hamsters bearing tumors induced by simian virus 40 tumor cells and from hamsters immune to tumor transplants was comparable to the response of lymphocytes from healthy donors.